Evaluasi Penggunaan Antibiotik untuk Terapi Infeksi Saluran Kemih (ISK) pada Pediatri di Instalasi Rawat Inap Rumah Sakit - Sermila Wulandari; Nera Umilia Purwanti; Ressi Susanti (State University of Gorontalo, 2022)
Urinary tract infection (UTI) is infection caused by the presence of microorganism in the urinary tract that multiply. Treatment of urinary tract infection can use antibiotic therapy andi if not done properly can cause resistance. This study aimed was to evaluate the use of antibiotics for the treatment of urinary tract infections in pediatrics at the Sultan Syarif Mohamad Alkadrie Inpatient Installation in January 2019-December 2020. This study is a descriptive observational research with a retrospective approach. The sampling technique used purposive sampling and the number of samples that met the inclusion criteria was 76 patients. Data obtained from medical records analyzed using Microsoft Excel based on 4T criteria ( right indication , right patient , right medicine , and right dose) refers to Guidelines On Urological Infections from European Association Of Urology Year 2015, Pediatric Dosage Handbook (PDH), and Guidelines for Medical Services of the Indonesian Pediatrician Association in 2009. The result showed that the evaluation the use of antibiotics was based on the right indications 100% (very good), right patient 100% (very good), right medicine 100% (very good), and right dose 55,3% (pretty good). The use of antibiotics for UTI patients at Sultan Syarif Mohamad Alkadrie Hospital still needs increased again , especially in terms of administering antibiotic dose.